Prototype multi-agent robotic debris removal system: principles of development and experimental studies - S. V. Manko; V. M. Lokhin; S. A. K. Diane (Российский технологический журнал)
Objectives. The article substantiates the relevance of the creation and the prospects of application of multi-agent robotic systems for elimination of consequences of emergency situations. The purpose of this work was to test the practical feasibility of algorithms for controlling a group of autonomous robots when performing multi-stage missions.Methods. The theses of the finite automata theory in planning actions of a multi-agent system, methods of automatic control in organizing a goal-directed movement of robots, and methods of computer vision in searching and analyzing debris geometry were used.Results. The principles of development, architecture, and composition are described for the software and algorithms of a prototype of the multi-agent robotic system created at RTU MIREA as part of integrated research for the creation of tools and methods of group control of robots. The multi-stage task of searching and removing debris in the process of eliminating the consequences of emergency situations is analyzed. A proposed algorithm for planning the actions of robotic agents determines the time sequence of the mission stages. Tasks are allocated among the performing robots according to assessments of their suitability. The autonomous functioning of robotic agents is determined by commands coming from the group control level, as well as an a priori embedded knowledge base with scenario models of appropriate actions. Compensation of local environmental uncertainties in the process of robot movement is based on a comprehensive analysis of visual and navigation information. Along with the main elements of the multi-agent system, the developed infrastructure of hardware and software for visual navigation and wireless communication is described.Conclusions. The results of the experimental studies demonstrated the efficiency of the developed approaches to the creation of intelligent technologies for group control of autonomous robots on the example of debris search and removal tasks. The feasibility of the multi-agent robotic system is demonstrated by the development and integration of a number of information management and infrastructure subsystems.